Corporate Social Responsibility in the Transport and Logistic Industry - Martina GOGOLOVA; Lukas VARTIAK (Communications of International Proceedings, 2021)
The paper deals with the concept of corporate social responsibility (CSR) in transport and logistics. It aims to analyse the CSR reports of FREJA – a responsible international transport and logistic company established in Denmark. FREJA CSR reports of 2017, 2018 and 2019 serve as main sources. To fulfil the aim of the paper, secondary research was conducted and methods of analysis, synthesis, abstraction, interpretation and statistics. As a result, seventeen focus areas of FREJA’S CSR strategy, including no poverty, zero hunger, good health and well-being, quality education, gender equality, clean water and sanitation, affordable and clean energy, decent work and economic growth, industry innovation and infrastructure, reduced inequalities, sustainable cities and communities, responsible consumption and production, climate action, life below water, life on land, peace and justice and strong institutions, partnership for the goals are to be identified.
Keywords: CSR; Transport; Logistic; FREJA; Ethics; ISO.